A Comparative Evaluation of the Experiential Approach as a Business Policy Learning Environment - Wolfe, Joe (Academy of Management Journal, 1975)
In a test of two teaching methods, the experiential group showed no improvement in overall knowledge or in fact or principle mastery. The traditional group increased its level of overall knowledge ...